Pelatihan Pengucapan Bunyi Konsonan Bahasa Inggris Kepada Mahasiswa BEC FBS UNM - Nasta, Mardiyanah; G, Hasriani; Asriati, Asriati; Risan, Rahmad (Jurnal Abdi Negeriku, 2022)
The use of a foreign language in communication takes more effort to avoid misunderstanding between the speaker and the listener who is notan English native speaker. The reason is a foreign language has different letters, pronunciation, and sentence structure. English which is well-known as an international language is an important language to master by Indonesian students to face the globalization. However, taught as a second language, many Indonesian still find it difficult to pronounce English sounds correctly. This workshop aims to reinforce the participants’ pronunciation, especially for English consonant sounds so they can pronoun the sounds correctly. This workshop was held using Google Meet because at that time social distancing was required and the college instructed all the learning process are conducted online. The participants showed positive attitude during the workshop and it was found some difficulties by students while practicing the English consonant sounds.